2022
DOI: 10.1021/acsomega.1c05488
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Biphasic Anatase-Rutile Ni-Pd/TNPs Nanocatalyst for the Reforming and Cracking Reactions of Microplastic Waste Dissolved in Phenol

Abstract: Solvent-based recycling of plastic can offer the main improvement when it is employed for pyrolysis-catalytic steam reforming. In this research, plastic waste dissolved in phenol was used as a feed for catalytic cracking and steam reforming reactions for valuable liquid fuels and hydrogen production, which is gaining the attention of researchers globally. Microplastic wastes (MPWs) are tiny plastic particles that arise due to product creation and breakdown of larger plastics. They can be found mainly in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 86 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…The broad peak of pure TiO2 nanoparticles located at 3238 cm −1 exhibited OH-stretching on the nanoparticles' surface, which absorbed the phenolic compounds, alcohols, and water molecules [36,37]. An aromatic ring vibration at the C=C stretching peak was seen at 1634 cm −1 , carboxylic acid formation was seen at 1524 cm −1 , and C-H asymmetric stretching from the plant derivatives was exhibited at the peak of 1417 cm −1 , which was derived from the zapota plant extract [38][39][40]. The wide peak at 759 cm −1 and the narrow peak at 553 cm −1 indicated the formation of activated carbon-loaded titanium dioxide nanoparticles and established the oxygen-metal-oxygen bonding [41].…”
Section: Ftir Analysismentioning
confidence: 99%
“…The broad peak of pure TiO2 nanoparticles located at 3238 cm −1 exhibited OH-stretching on the nanoparticles' surface, which absorbed the phenolic compounds, alcohols, and water molecules [36,37]. An aromatic ring vibration at the C=C stretching peak was seen at 1634 cm −1 , carboxylic acid formation was seen at 1524 cm −1 , and C-H asymmetric stretching from the plant derivatives was exhibited at the peak of 1417 cm −1 , which was derived from the zapota plant extract [38][39][40]. The wide peak at 759 cm −1 and the narrow peak at 553 cm −1 indicated the formation of activated carbon-loaded titanium dioxide nanoparticles and established the oxygen-metal-oxygen bonding [41].…”
Section: Ftir Analysismentioning
confidence: 99%
“…The surface area and micro-pore volume of 4% Ni/SAPO-11-L, 4% Ni/SAPO-11-LZ and 4% Ni/SAPO-11-LLZ were higher than those of 4% Ni/SAPO-11, attributed to the weaker blockage of metal species with higher metal dispersion. 6,37 Especially for 4% Ni/SAPO-11-LLZ, its surface area and micro-pore volume were 30% and 32% higher than those of 4% Ni/SAPO-11, respectively. This can be attributed to the fact that the metal is ultra-small and evenly dispersed, and therefore expose more channels.…”
Section: Resultsmentioning
confidence: 95%
“…In another study, small plastic fragments on the northeast Brazilian coast were collected and recycled to prepare the recycled materials [ 176 ]. A Ni–Pd/TNPs nanocatalyst was prepared, which could be used for catalytic cracking MPs-phenol and steam reforming reaction to generate valuable liquid products and hydrogen fuel [ 177 ]. A new study reported an electrocatalytic upcycling strategy for PET waste to produce valuable H 2 , terephthalic acid (PTA), and potassium diformate (KDF) [ 178 ].…”
Section: Recycling Of Mpsmentioning
confidence: 99%